GAMBARAN KEBIMBANGAN KARIER PADA MAHASISWA TINGKAT AKHIR DI UNIVERSITAS NEGERI PADANG BERDASARKAN PROGRAM STUDI DAN JENIS KELAMIN - priyangga, yogi (CV. Causalita Dynamic Solutions, 2024)
Higher education is a formal educational institution that provides formal education with the aim of producing students with graduates who have skills, commendable character, quality and are ready to enter the world of work. However, in this process final year students are often faced with various challenges. One of these challenges is career indecision. This research was conducted with the aim of finding out the description of career indecision among final year students at Padang State University based on study program and gender. This research was studied using quantitative research with a comparative approach. Data collection was carried out using a questionnaire technique distributed via Whatsapp and Instagram to 277 respondents from 9 study programs at Padang State University. The data analysis technique in this research was carried out using the t-test, one way anova and two way anova. The results obtained in this research indicate that career indecision among final year students at Padang State University is in the low category. This research illustrates that final year students at Padang State University have sufficient motivation regarding career-related decision making. Apart from that, final year students also have sufficient information about matters relating to themselves or the world of work they will be involved in, and there are also no internal or external conflicts within the subject in determining his career choice.